Analisis Sektor Ekonomi Potensial Kabupaten Batang Hari - Wiyan Mailindra (CITRA EKONOMI, 2020)
This research uses LQ Analysis Tool, and Pearson Correlation. As for the operating variable in this study is the GDP at constant prices, Economic Growth, Growth Sector, And Poverty in Batanghari, with the title "Analysis of Potential Sectors and Relation to Poverty in Batanghari" This aims to determine the potential economic sector in Batanghari and see the relationship of each sector of the economy with poverty. The final conclusion that can be drawn in the study is based on the analysis contained LQ potential sector in Batanghari is the mining and quarrying sector with a value of LQ> 1, while other economic sectors has LQ <1. Then, the results of Pearson Correlation between the overall Growth economic with poverty can result in a positive and strong enough, then the results of Pearson Correlation Sectoral economic growth with poverty, the mining sector has a value of Pearson Correlation highest and the associated positive and strong enough, and that the lowest is the relationship with the trade sector but remain positively related poverty and less powerful.